Supramolecular organic frameworks with ultralong phosphorescence via breaking π-Conjugated structures - Wei Yao; Chaoqun Ma; Huili Ma; Lishun Fu; Song Lu; Anqi Lv; Suzhi Cai; Xiaochun Hang; Manjeet Singh; Huifang Shi; Zhongfu An; Wei Huang (Giant, 2020)
Development of crystalline porous materials with luminescent properties have gradually attracted attention for their potential applications in drug delivery, bioimaging, photoelectronic and so on. To date, it is a formidable challenge to rationally design porous phosphorescent materials. Herein, we have reported a chemical strategy of breaking π-conjugated structures of phosphorescent molecules by alkyl chain to achieve supramolecular organic framework (SOFs) with visible ultralong phosphorescence (lifetime > 600 ms). The molecules having broken π-conjugation by flexible alkyl chain will be beneficial to produce short-range π-π stacking for forming luminescent SOFs. Effective π-π stacking between chromophores stabilized triplet excitons to contribute to ultra-long phosphorescence. This work demonstrates a new approach to design porus materials with ultralong phosphorescence and will expand the potential applications of organic phosphorescent crystals with diverse pores.